Living “here” and “there”: Considering the Pre-Migration and Settlement Related Transnational Information Practices of Newcomers from the Philippines to Winnipeg - Allard, Danielle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This research investigates the role that transnational information practices play in the “everyday information practices” of Filipino newcomers to Winnipeg. It examines how newcomers navigate global (and local) social networks, information institutions, and resources during departure from the Philippines and reception into Canada to find information to settle and live in Winnipeg. Cette recherche porte sur le rôle que jouent les pratiques informationnelles transnationales dans les « pratiques informationnelles quotidiennes » d’immigrants philippins à Winnipeg. On y examine comment les nouveaux arrivants naviguent sur les réseaux sociaux mondiaux (et locaux), utilisent les services d’institutions d’information et leurs ressources au départ des Philippines et à leur arrivée au Canada afin de trouver de l’information pour se relocaliser et s’établir à Winnipeg.